Endurance training is feasible in severely disabled patients with progressive multiple sclerosis. (April 2014) - Skjerbæk, AG; Næsby, M; Lützen, K; Møller, AB; Jensen, E; Lamers, I; Stenager, E; Dalgas, U
This study tested whether upper-body endurance training (ET) is feasible and can be performed at sufficient intensity to induce cardiovascular adaptations in severely disabled patients with progressive multiple sclerosis (MS). Eleven progressive MS patients (6.5 ≤ EDSS ≤ 8.0) scheduled for a four-week inpatient rehabilitation program were randomized to a control group (CON, n = 5) that received standard individualized MS rehabilitation or an intervention group (EXE, n = 6) that in addition received 10 sessions of predominantly upper-body ET. One patient dropped out of the EXE group (drop-out rate: 1/6 17%) and no adverse events were recorded. The EXE group completed on average 9.3±0.8 sessions ( 96.0±5%). During the ET sessions an average heart rate of 93.9±9.3beats*min –1 were sustained corresponding to 91.6±6.8% of the maximal pre-intervention heart rate. In the EXE group a trend toward a time*group interaction was seen for VO2peak ( p = 0.06). ET is feasible in severely disabled patients with progressive MS and it can probably be performed at sufficient intensity to induce cardiovascular adaptations.